Autologous cytokine-induced killer (CIK) immunotherapy in a case of disseminated tuberculosis - ping, xu; junchi, xu; xinnian, chen; zhijian, ye; meiying, wu (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
A 23-year-old woman had dry cough, fever and chest tightness for 1 months. Through thoracic CT scan and serological examination, the patient was clinically diagnosed as disseminated tuberculosis. she was given anti-tuberculosis therapy combined with autologous cytokine-induced killer (CIK) immunotherapy. Through the close follow-ups we found that after immunotherapy Her condition would have a swift improvement and she do not appear liver damage after a large doses of antibiotic therapy. In conclusion, adjuvant autologous CIK immunotherapy is an effective approach for disseminated tuberculosis.